2022
DOI: 10.15252/emmm.202215829
|View full text |Cite
|
Sign up to set email alerts
|

FIBCD1 is an endocytic GAG receptor associated with a novel neurodevelopmental disorder

Abstract: Whole‐exome sequencing of two patients with idiopathic complex neurodevelopmental disorder (NDD) identified biallelic variants of unknown significance within FIBCD1, encoding an endocytic acetyl group‐binding transmembrane receptor with no known function in the central nervous system. We found that FIBCD1 preferentially binds and endocytoses glycosaminoglycan (GAG) chondroitin sulphate‐4S (CS‐4S) and regulates GAG content of the brain extracellular matrix (ECM). In silico molecular simulation studies and GAG b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…The 2 most highly upregulated genes in the beneficial group are CG15263 (no human ortholog) and CG6788 ( FIBCD1 ) (Log 2 (fold change) = 8.27 and 4.04, respectively) ( Hu et al 2011 ). While the function of CG6788 is unknown, loss of function mutations in FIBCD1 is associated with neurodevelopmental disorders in humans ( Fell et al 2022 ). CG6788 may also play a role in neurodevelopment in Drosophila.…”
Section: Resultsmentioning
confidence: 99%
“…The 2 most highly upregulated genes in the beneficial group are CG15263 (no human ortholog) and CG6788 ( FIBCD1 ) (Log 2 (fold change) = 8.27 and 4.04, respectively) ( Hu et al 2011 ). While the function of CG6788 is unknown, loss of function mutations in FIBCD1 is associated with neurodevelopmental disorders in humans ( Fell et al 2022 ). CG6788 may also play a role in neurodevelopment in Drosophila.…”
Section: Resultsmentioning
confidence: 99%
“…The Ncan gene encodes for a CSPG neurocan, the main component of perineuronal nets stabilizing synapses. A very recent study has identified the fibrinogen C domain containing 1 (FIBCD1) as an endocytic receptor for CSPGs predominantly expressed in the CA1 area of the hippocampus within the brain [ 39 ]. Thus, the PSEN1 ΔE9 mutation in transplanted human glia dysregulated the expression of CSPG signaling molecules in the mouse hippocampus.…”
Section: Resultsmentioning
confidence: 99%
“…A genetic variant in the human NCAN gene increasing the level of neurocan expression was recently found to be associated with worsened hippocampal memory function in healthy humans [ 66 ]. Moreover, FIBCD1 has recently been demonstrated to be involved in hippocampal-dependent learning in mice [ 39 ]. Altogether, these gene expression changes are in line with better spatial memory function in PSEN1 ΔE9-mutant glia-transplanted mice observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Fibcd1 encodes a receptor for endocytosed glycosaminoglycans in the brain, and plays a role in nervous system structure, function and plasticity. Knocking down Fibcd1 leads to idiopathic complex neurodevelopmental disorder (NDD) (Fell et al 2022). Eng2b is involved in the localization of diencephalon-mesencephalon boundary during brain development (Rampon et al 2015).…”
Section: Discussionmentioning
confidence: 99%